KOMPARASI STRUKTUR DAN PERKEMBANGAN UBUR-UBUR BINTIK (Mitiagas papua) DAN UBUR-UBUR BULAN (Aurelia aurita) SEBAGAI RESPONS ADAPTIF TERHADAP PERBEDAAN LINGKUNGAN - Yeni Ismawati (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2026)
Mastiagas papua and Aurelia aurita are two scyphozoan jellyfish species that differ in body structure, development, and environmental adaptation. This study aims to compare the characteristics of both species based on a literature review. The review was conducted through the collection of relevant scientific articles and analyzed descriptively-comparatively. The results showed that Mastiagas papua has a thicker and denser body, a golden coloration, shorter tentacles that are less active in capturing prey than those of Aurelia aurita, and a symbiotic relationship with zooxanthellae that makes it highly dependent on light and stable environmental conditions. In contrast, Aurelia aurita has a thinner and more transparent body, longer tentacles, and a more complex and flexible life cycle, allowing it to adapt to a wider range of aquatic environments. These differences indicate that the body structure and development of the two species are closely related to their respective habitat adaptation strategies.